PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP PENGURANGAN RASA NYERI PADA PERSALINAN KALA I DI WILAYAH PUSKESMAS KLEGO I BOYOLALI - ., Rosalinna (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Labor pain is part of a normal process, which often causes physiological and psychological stress to mother. One of Non-pharmacological approach to reduce labor pain used Lavender Aromatherapy. This research aims to know an Influence of Lavender Aromatherapy to reduce Pain in Labor Active Phase at Klego I primary health service of Boyolali. Design study use a quasi experiment, design used pre and post test without control. The sample was 54 labor women Active Phase at Klego I primary health service of Boyolali, taking sample used purposive sampling.  Instrument study used Lavender Aromatherapy about 0,3 ml and measurement of pain uses pain numerical ratings scale questionnaire.  An analysis of data using wilcoxon test. Average labor pain before respondents given Lavender Aromatherapy was 8,50±0.9 (all respondents with severe pain.  After respondents    had given Lavender Aromatherapy   was   6,11±1,23 (15 respondents with moderate pain) result of Wilcoxon test with z = -5.939 p = 0,000 (p< 0,05). There was an Influence of Lavender Aromatherapy to reduce Pain in Labor Active Phase at Klego I primary health service of Boyolali. Keyword: Lavender Aromatherapy, Pain in Labor, Active Phase